Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.18203/2394-6040.ijcmph20205158
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practices towards COVID-19 among healthcare workers of Karnataka, India: a cross-sectional survey

Abstract: Background: COVID-19 is a Public health emergency of international concern which has affected over 213 countries infecting millions across the globe and also affected the economy worldwide. This study was conducted in Healthcare Workers as they are the frontline warriors in fighting this pandemic and their knowledge, attitude and practices towards the disease are valuable.Methods: Online cross sectional study was conducted on Healthcare Workers. A self-administered Google form was used to collect the data thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 4 publications
(6 reference statements)
0
6
1
Order By: Relevance
“…Similar independent association was observed in a studies related to COVID-19. 20,21 However, the present study didn't show significant association with age and years of experience as observed in previous studies. This could be explained as the COVID-19 is a novel disease with limited and accurate resources, about management of viral hepatitis patients during COVID-19, hence age and experience couldn't have a role in increasing the knowledge related to management of viral hepatitis patients during COVID-19.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Similar independent association was observed in a studies related to COVID-19. 20,21 However, the present study didn't show significant association with age and years of experience as observed in previous studies. This could be explained as the COVID-19 is a novel disease with limited and accurate resources, about management of viral hepatitis patients during COVID-19, hence age and experience couldn't have a role in increasing the knowledge related to management of viral hepatitis patients during COVID-19.…”
Section: Discussioncontrasting
confidence: 65%
“…15,20 Another study from India reported a higher knowledge as compared to the present study, this could be attributable to variation in the questionnaire. 21 The knowledge score in pre knowledge assessment was found to be significantly associated with factors such as gender, years of experience, geographical location, type of facility working and educational qualification of the participants. However, only gender, type of facility working and educational qualification of the participants were found to be independently associated after adjusting for various other factors.…”
Section: Discussionmentioning
confidence: 91%
“…As we all know, to establish preventive thoughts, affirmative attitudes, and positive practices, knowledge is a definite prerequisite. [12][13][14][15][16] Personal cognition can be shaped in such way where the healthcare worker can cope up with much more insight. 23 The present study complies with the fact that knowledge can induce positive attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…23 The present study complies with the fact that knowledge can induce positive attitudes. [13][14][15][16] A healthcare worker can impart more confidence in dealing with the virus if one has sufficient knowledge. This finding, as mentioned in table 5, is at par with prior studies on similar topic from different parts of the world 9,12,14,15 as well as in India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation